2015
DOI: 10.1007/s11307-015-0853-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an mKate2-Expressing Cell Line for Non-Invasive Real-Time Breast Cancer In Vivo Imaging

Abstract: In the present research, we have successfully built the MDA-MB-435s-mKate2 cell line that can be used as a suitable cell model for breast cancer therapy and anti-cancer drug evaluation by non-invasive fluorescence imaging in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It has been reported that the expression of mKate-2 and luciferase have no effect on the biological behavior of parental cell. 18,19 Bioluminescence imaging (BLI) analysis confirmed that the light intensity, released from the VNP20009 strain expressing luciferase (“VNP20009-luc”), was proportional to bacterial counts (r 2 = 0.99). Additionally, VNP20009-luc displayed 0.36 ± 0.035 flux units per cfu in vitro ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…It has been reported that the expression of mKate-2 and luciferase have no effect on the biological behavior of parental cell. 18,19 Bioluminescence imaging (BLI) analysis confirmed that the light intensity, released from the VNP20009 strain expressing luciferase (“VNP20009-luc”), was proportional to bacterial counts (r 2 = 0.99). Additionally, VNP20009-luc displayed 0.36 ± 0.035 flux units per cfu in vitro ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Bioluminescence imaging experiments were performed on a home-made imaging system [18]. Briefly, experimental mice were injected intraperitoneally with 150 mg/kg D-luciferin (15 mg/mL in sterile DPBS) at predetermined time points.…”
Section: Bioluminescent Imagingmentioning
confidence: 99%
“…As a far-red fluorescent protein, higher brightness characterizes mKate2 and greater tissue penetration. It has, therefore, been widely used for labeling cells in vitro and real-time monitoring in vivo (15,16). In brief, the ADSCs were seeded into 24-well plates (20,000/well) and grown to 30-50% confluence.…”
Section: Labeling Of Adscsmentioning
confidence: 99%